One-step silane crosslinked SEBS-based elastomer and preparation method thereof

By granulating SEBS powder and adopting blending technology, the problem of SEBS-based elastomer deformation at high temperature is solved, and the energy consumption and time of traditional processes are reduced, thus achieving rapid, efficient and low-energy production of SEBS-based elastomer, satisfying the Develop application requirements in high temperature environments.

CN119463345APending Publication Date: 2025-02-18GUANGDONG ZHONGDE CABLE +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411595538.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-08
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing SEBS-based elastomer materials are prone to deform at high temperatures, and the traditional one-step silane crosslinked polyethylene process consumes time and energy, making it difficult to meet the insulating materials for electronic wires, new energy vehicle charging pile cables and in-vehicle connection cables. Require.

Method used

By granulating the raw material of SEBS powder and blending a small amount of powder with the waste heat particle substrate, combined with optimized formula and process design, one-step silane cross-linking of SEBS-based elastomers is achieved, reducing the production process Energy consumption and time.

Benefits of technology

It realizes rapid, efficient and low-energy production of SEBS-based elastomers, improves the heat resistance and flexibility of the material, meets the application needs in high-temperature environments, and significantly reduces the energy consumption of the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126798510000081
    Figure BDA0005126798510000081
  • Figure BDA0005126798510000091
    Figure BDA0005126798510000091
Patent Text Reader

Abstract

The invention discloses a one-step silane crosslinked SEBS-based elastomer and a preparation method thereof. The elastomer is composed of a silane master batch and a catalytic master batch. Wherein the silane master batch is prepared from the following components in parts by weight: 40 to 60 parts of SEBS (Styrene-Ethylene-Butylene-Styrene), 40 to 60 parts of linear low-density polyethylene, 1.5 to 5.0 parts of vinyl silane, 0.03 to 0.25 part of initiator, 20 to 30 parts of processing base oil, 0.5 to 1.0 part of lubricant and 1.0 to 5.0 parts of antioxidant; the catalytic master batch comprises the following components in parts by weight: 99 parts of linear low-density polyethylene, 1 part of SEBS, 1.5-2.5 parts of a catalyst and 2.0 parts of an antioxidant; after the silane master batch and the catalytic master batch are prepared, the silane master batch and the catalytic master batch are packaged according to the proportion of 19: 1, and a finished product is obtained. According to the invention, the one-step rapid, efficient and low-energy-consumption preparation of the silane crosslinked SEBS-based elastomer is realized, the production efficiency is improved, the production cost is reduced, the energy is saved, and the preparation process is greener and lower in carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a one-step silane cross-linked styrene-ethylene / butylene-styrene block copolymer (SEBS)-based elastomeric material, which meets the requirements of insulating materials for electronic wires, new energy vehicle charging pile cables and in-vehicle connecting cables, and belongs to the technical field of polymer materials. The present invention also relates to a preparation method of the above-mentioned elastomeric material. Background Art

[0002] SEBS-based elastomer materials have good flexibility and a wide range of adjustable hardness, and are widely used in consumer electronics, new energy and other daily necessities. However, thermoplastic elastomer materials are prone to plastic deformation in high temperature environments. Generally, they will deform at a temperature of 150°C and a certain pressure, and are only suitable for use in situations where heat resistance requirements are not high. Thermoplastic elastomer materials are not suitable for situations where the instantaneous temperature is high and the elastomer is prone to deformation and failure. Cross-linking is required to improve the heat resistance of the material. The cross-linked elastomer can withstand instantaneous high temperatures of 200°C or even 250°C.

[0003] The hardness of commonly used silane cross-linked polyethylene is generally around 97A or 50D. For conventional cable applications, the hardness has no obvious effect on the wiring because of the large wiring space. However, for applications such as automobiles and electrical equipment where the wiring space is small, excessive cable hardness will seriously affect the wiring. The hardness of SEBS-based elastomers can be adjusted in a very wide range: it can be used as a toughening agent to blend with the original silane cross-linked polyethylene to slightly reduce the hardness of the silane cross-linked polyethylene; it can also be used as the main material to obtain a lower hardness or even a hardness below 60A.

[0004] The process of one-step silane cross-linked polyethylene generally includes heating of drying silo, drying of base material, heating of shake tank, vacuuming of shake tank, inhalation of silane and nitrogen, silane adsorption, etc. Directly using the process of one-step silane cross-linked polyethylene can also achieve silane cross-linking of SEBS-based elastomers, but the whole process takes about 120 minutes, and the equipment also needs to be heated, which is time-consuming and energy-consuming.

[0005] Therefore, in order to realize the one-step silane cross-linking of SEBS-based elastomers, it is necessary to improve the form of the raw materials of SEBS-based elastomers, optimize the formula and process, realize the rapid, efficient and low-energy production of SEBS-based elastomers, solve the problem that the SEBS-based elastomer powder raw materials cannot be used directly (SEBS is a powdery raw material, and direct use in cable production will bring in too much gas, resulting in more pores in the extruded insulation or sheath layer, which seriously affects the cable performance and cannot be used), and solve the time-consuming and energy-consuming problem of the traditional one-step silane cross-linking polyethylene process. Summary of the invention

[0006] The purpose of the present invention is to provide a one-step silane cross-linked SEBS-based elastomer, which adopts a method of first forming SEBS powder raw materials into particles, thereby solving the problem that SEBS powder raw materials are inconvenient to use in cable production; a small amount of powder is blended with a residual heat particle substrate, etc., thereby solving the problem of energy and time consumption of drying and adsorption processes in the traditional one-step silane cross-linked polyethylene process, and realizing rapid, efficient and low-energy production of SEBS-based elastomers. The present invention also provides a preparation method of the above one-step silane cross-linked SEBS-based elastomer.

[0007] To achieve the above object, the technical solution of the present invention is:

[0008] One-step silane cross-linked SEBS-based elastomer, which consists of two parts: a silane masterbatch and a catalytic masterbatch, wherein the mass ratio of the silane masterbatch to the catalytic masterbatch is 19:1;

[0009] The silane masterbatch comprises the following components by weight: 40-60 parts of SEBS (silane cross-linked styrene-ethylene / butylene-styrene block copolymer), 40-60 parts of linear low-density polyethylene (LLDPE), 1.5-5.0 parts of vinyl silane, 0.03-0.25 parts of initiator, 0.5-1.0 parts of lubricant, 20-30 parts of processing base oil, and 1.0-5.0 parts of antioxidant;

[0010] The catalytic masterbatch comprises the following components in parts by weight: 99 parts of linear low-density polyethylene (LLDPE), 1 part of SEBS, 1.5-2.5 parts of catalyst, and 2.0 parts of antioxidant.

[0011] Specifically, in order to improve the process performance of the product, SEBS is a medium-to-low molecular weight product (molecular weight of 80,000 to 180,000). Too high a molecular weight will make the process performance of SEBS, which already has poor process performance, even worse. In order to improve the compatibility of LLDPE and SEBS, the ethylene and butene segment content of SEBS is appropriately higher, so the styrene content is about 18wt%.

[0012] In order to comprehensively consider the process flow properties, uniformity of blending and dispersion, surface effects and other properties of the finished product, the mass flow rate of the linear low-density polyethylene melt (190°C, 2.16kg) is 1-3g / 10min.

[0013] In order to reduce volatilization during processing and use, the flash point of the processing base oil is above 260°C.

[0014] For the convenience of use and storage, dicumyl peroxide (DCP) with a relatively long half-life is selected as the initiator.

[0015] In order to reduce the cross-linking side reaction of the carbon-carbon bonds in the main chain of the substrate during the grafting process, and comprehensively consider the antioxidant efficiency, copper damage, cost and other factors of the finished product, the antioxidants in the silane masterbatch and the catalyst masterbatch are antioxidants 1010, 168, and 1024 compounded in a ratio of 1:1:1.

[0016] The vinyl silane is vinyl trimethoxy silane. Since it does not contact water during the process, the risk of premature hydrolysis of silane in the product to produce pre-crosslinking is small. After silane grafting is achieved in the cable production process, the crosslinking speed is increased as much as possible. The hydrolysis rate of silane is an important influencing factor, so vinyl trimethoxy silane with a higher hydrolysis rate is selected. Vinyl methoxyethoxy silane and vinyl triethoxy silane with a slower decomposition rate are not within the selection range.

[0017] The lubricant is a commonly used PE-based silicone masterbatch, wherein the silicone content is 50wt%.

[0018] The catalyst is dibutyltin dilaurate. In addition, there are other optional catalysts, such as benzenesulfonic acid catalysts, but in a system without fillers, the effect of organic tin catalysts is more effective and stable, so organic tin catalysts are preferred.

[0019] The one-step silane cross-linked SEBS-based elastomer preparation method comprises the following steps:

[0020] (1) Preparation of silane masterbatch

[0021] LLDPE, lubricant, antioxidant, 99wt% SEBS powder and processing base oil are sequentially added to a high-speed mixer and stirred evenly to allow SEBS to fully absorb the processing base oil, and then the materials are added to an internal mixer and internally kneaded to 140-160° C. to fully plasticize the materials, and then the material mass is poured into a conical feeder, and granulated by twin-screw and single-screw extrusion. The particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc. When the particles are cooled to no more than 50° C., the particles are added to the high-speed mixer, and the remaining 1wt% SEBS powder is added at the same time, and then vinyl silane dissolved with an initiator is added. After the silane is added, it is stirred for 1 minute, and then vacuum-packed to obtain a silane masterbatch;

[0022] (2) Preparation of catalytic masterbatch

[0023] The linear low-density polyethylene, SEBS powder, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer for internal mixing at 140-160°C to fully plasticize the material. The material mass is then poured into a conical feeder for granulation through twin-screw and single-screw extrusion. The particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc., and then vacuum packaged to obtain a catalytic masterbatch.

[0024] (3) Packing the silane masterbatch and the catalyst masterbatch separately according to the ratio to obtain the finished product

[0025] During cable production, separate the silane masterbatch and the catalyst masterbatch, pour them into a mixer and mix them evenly before use.

[0026] In order to realize one-step crosslinking and rapid, efficient and low-energy production of SEBS-based elastomers, the present invention adopts the following technical solutions:

[0027] (1) Formulation design

[0028] Compared with conventional SEBS elastomer materials, polypropylene and propylene-based elastomers are replaced with polyethylene. Because polypropylene is mainly degraded under the action of initiators and it is difficult to form grafts, the high melt index polypropylene used for meltblown cloth is made by degrading low melt index polypropylene based on this principle.

[0029] In the selection of SEBS, SEBS with slightly higher ethylene and butene content is selected to increase its compatibility with polyethylene. Conventional thermoplastic SEBS-based elastomers mainly consider the compatibility of SEBS with polyphenylene ether and polypropylene, while these components are changed to polyethylene in the composition of the present invention. In order to obtain a product with better performance, the compatibility of each component is a factor that must be considered.

[0030] In the formula design of the catalytic masterbatch, compared with the traditional silane cross-linked polyethylene catalytic masterbatch, an appropriate proportion of SEBS powder is added to the formula, which plays the role of absorbing liquid catalysts during the production process, making it easier to change the water-drawn strip production method to a hot-cut production method, which not only improves production efficiency, but also reduces the introduction of moisture and reduces the dehydration and drying environment.

[0031] (2) Process design

[0032] First, the powdered SEBS is granulated so that it can be adsorbed with silane using a process similar to the one-step silane cross-linking polyethylene process, solving the problem of the inconvenience of using the powder in the production of wires and cables.

[0033] Secondly, the hot cutting granulation and air cooling process can directly remove the moisture that may be contained in the raw materials, and avoid the contact between particles and water in processes such as water ring cutting and water strand granulation, eliminating the dehydration and drying process, saving water resources, reducing the moisture in the particles, and minimizing the pre-crosslinking problem caused by moisture.

[0034] (3) The use of a homogenizing silo not only improves product consistency, but also reduces the temperature of the pellets, preventing soft product particles from sticking together.

[0035] (4) The process of using a high-speed mixer to mix a small amount of powdered SEBS with granular materials to absorb silane has greatly improved the speed and uniformity of silane adsorption. This process not only has a fast silane adsorption speed and high uniformity, but also eliminates the material heating, vacuuming, and nitrogen filling processes in the one-step silane cross-linked polyethylene process. DETAILED DESCRIPTION

[0036] In Examples 1-3, SEBS is a medium-low molecular weight product, wherein the styrene content is about 18wt%; the melt mass flow rate of LLDPE (190°C, 2.16kg) is 1-3g / 10min; the initiator is diisopropylbenzene peroxide (DCP); the lubricant is a PE-based silicone masterbatch, wherein the silicone content is 50wt%; the flash point of the processing base oil is above 260°C; the antioxidant is antioxidants 1010, 168, and 1024 compounded in a ratio of 1:1:1; and the catalyst is dibutyltin dilaurate.

[0037] Example 1

[0038] (1) Silane masterbatch composition: SEBS 40 parts, LLDPE 60 parts, vinyl trimethoxy silane 1.5 parts, initiator 0.03 parts, lubricant 1.0 parts, processing base oil 20 parts, antioxidant 1.0 parts;

[0039] The preparation process of the silane masterbatch is as follows: LLDPE, lubricant, antioxidant, 99wt% SEBS powder and processing base oil are added to a high-speed mixer and stirred evenly to make SEBS fully absorb the processing base oil, and then the materials are added to an internal mixer, and the internal mixer is kneaded to 140°C to make the materials fully plasticized, and then the material mass is poured into a conical feeder, and granulated by twin-screw and single-screw extrusion, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc. When the particles are cooled to no more than 50°C, the particles are added to the high-speed mixer, and the remaining 1wt% SEBS powder is added at the same time, and then vinyl trimethoxy silane dissolved with an initiator is added while stirring, and after the silane is added, it is stirred for 1 minute, and then vacuum-packed to obtain the silane masterbatch.

[0040] (2) The composition of the catalytic masterbatch is: 99 parts of LLDPE, 1 part of SEBS, 2.5 parts of catalyst, and 2.0 parts of antioxidant.

[0041] The preparation process of the catalytic masterbatch is as follows: LLDPE, SEBS powder, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer for internal mixing at 160°C to fully plasticize the material. The material mass is then poured into a conical feeder for granulation through twin-screw and single-screw extrusion. The particles are cooled and homogenized through pipelines, cyclone separators, vibrating screens, homogenizing silos, etc., and then vacuum packaged to obtain the catalytic masterbatch.

[0042] The silane masterbatch and the catalyst masterbatch were mixed and stirred at a ratio of 19:1, and then extruded into a sheet in an extruder. The obtained sheet was cross-linked in 80°C hot water for 4 hours, and then cut into samples to obtain test samples. The material properties are shown in Table 1.

[0043] Example 2

[0044] (1) Silane masterbatch composition: SEBS 50 parts, LLDPE 50 parts, vinyl trimethoxy silane 3.2 parts, initiator 0.14 parts, lubricant 0.75 parts, processing base oil 25 parts, antioxidant 3.0 parts;

[0045] The preparation process of the silane masterbatch is as follows: LLDPE, lubricant, antioxidant, 99wt% SEBS powder and processing base oil are added to a high-speed mixer and stirred evenly to allow SEBS to fully absorb the processing base oil, and then the materials are added to an internal mixer, internally kneaded to 150°C to fully plasticize the materials, and then the material mass is poured into a conical feeder, extruded and granulated by a twin-screw or single-screw extruder, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc. When the particles are cooled to no more than 50°C, the particles are added to the high-speed mixer, and the remaining 1wt% SEBS powder is added at the same time, and then vinyl trimethoxy silane dissolved with an initiator is added while stirring, and after the silane is added, it is stirred for 1 minute, and then vacuum-packed to obtain the silane masterbatch.

[0046] (2) The composition of the catalytic masterbatch is: 99 parts of LLDPE, 1 part of SEBS, 2.0 parts of catalyst, and 2.0 parts of antioxidant.

[0047] The preparation process of the catalytic masterbatch is as follows: LLDPE, SEBS powder, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer for internal mixing at 150°C to fully plasticize the material. The material mass is then poured into a conical feeder for granulation through twin-screw and single-screw extrusion. The particles are cooled and homogenized through pipelines, cyclone separators, vibrating screens, homogenizing silos, etc., and then vacuum packaged to obtain the catalytic masterbatch.

[0048] The silane masterbatch and the catalyst masterbatch were mixed and stirred at a ratio of 19:1, and then extruded into a sheet in an extruder. The obtained sheet was cross-linked in 80°C hot water for 4 hours, and then cut into samples to obtain test samples. The material properties are shown in Table 1.

[0049] Example 3

[0050] (1) Silane masterbatch composition: SEBS 60 parts, LLD vinyl trimethoxy silane 5.0 parts, initiator 0.25 parts, lubricant 0.5 parts, processing base oil 30 parts, antioxidant 5.0 parts;

[0051] The preparation process of the silane masterbatch is as follows: LLDPE, lubricant, antioxidant, 99wt% SEBS powder and processing base oil are added to a high-speed mixer and stirred evenly to allow SEBS to fully absorb the processing base oil, and then the materials are added to an internal mixer, internally kneaded to 160°C to fully plasticize the materials, and then the material mass is poured into a conical feeder, extruded and granulated by a twin-screw or single-screw extruder, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc. When the particles are cooled to no more than 50°C, the particles are added to the high-speed mixer, and the remaining 1wt% SEBS powder is added at the same time, and then vinyltrimethoxysilane dissolved with an initiator is added, and after the silane is added, it is stirred for 1 minute, and then vacuum-packed to obtain the silane masterbatch.

[0052] (2) The composition of the catalytic masterbatch is: 99 parts of LLDPE, 1 part of SEBS, 1.5 parts of catalyst, and 2.0 parts of antioxidant.

[0053] The preparation process of catalytic masterbatch is as follows: LLDPE, SEBS powder, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer for internal mixing at 140°C to fully plasticize the material. The material mass is then poured into a conical feeder for granulation through twin-screw and single-screw extrusion. The particles are cooled and homogenized through pipelines, cyclone separators, vibrating screens, homogenizing silos, etc., and then vacuum packaged to obtain the catalytic material.

[0054] The silane masterbatch and the catalyst masterbatch were mixed and stirred at a ratio of 19:1, and then extruded into a sheet in an extruder. The obtained sheet was cross-linked in 80°C hot water for 4 hours, and then cut into samples to obtain test samples. The material properties are shown in Table 1.

[0055] Comparative Example 1:

[0056] Compared with the embodiment, in comparative example 1, SEBS with a molecular weight exceeding 400,000 is used, and silane is vinyl triethoxy silane. Other compositions and processes are the same as those in embodiment 1.

[0057] Comparative Example 2:

[0058] The silane masterbatch components of Comparative Example 2 are the same as those of Example 1, and the composition and preparation process of the catalytic masterbatch are also the same as those of Example 1. The difference from Example 1 is that the preparation of the silane masterbatch adopts a process similar to that of one-step silane cross-linked polyethylene, specifically:

[0059] (1) During the preparation of the silane masterbatch, when the raw materials are mixed at a high speed, 1 wt% of SEBS is no longer retained. Instead, all of the SEBS is added to the high speed mixer for mixing before granulation.

[0060] (2) During the preparation of the silane masterbatch, when the particles absorb silane, no powdered SEBS is added, but all the particles are prepared. The preparation is similar to the one-step silane cross-linking polyethylene method, specifically: (a) The shaking tank is sealed and the water in the water tank is heated so that the hot water maintains the heating of the tank body. After the tank body reaches the set temperature, the prepared particles are added, and then vacuum is drawn, silane is inhaled, nitrogen is inhaled, and rotation and stirring are maintained for 70 minutes to obtain the silane masterbatch.

[0061] The main difference between Comparative Example 2 and the embodiment and Comparative Example 1 lies in the process of silane adsorption: In Comparative Example 2, 100wt% of SEBS powder, LLDP, lubricant, antioxidant and processing base oil are added to a high mixer and stirred evenly to allow SEBS to fully absorb the processing base oil, and then the materials are added to an internal mixer to fully plasticize the materials, and then the material mass is poured into a conical feeder, extruded and granulated by a twin-screw or single-screw extrusion, and the particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc.; Silane adsorption process: the prepared particles are added to a shaking tank, the shaking tank is sealed and the water in the water tank is heated so that the hot water maintains the heating of the tank body, and after the tank body reaches the set temperature, the prepared particles are added, and then vacuum is drawn, silane is inhaled, nitrogen is inhaled, and rotation and stirring are maintained for 70 minutes to obtain a silane masterbatch. In Examples 1-3 and Comparative Example 1, 99 wt % of SEBS powder, LLDPE, lubricant, antioxidant and processing base oil are added to a high-speed mixer and stirred evenly to allow SEBS to fully absorb the processing base oil. The materials are then added to an internal mixer to fully plasticize the materials. The material mass is then poured into a conical feeder and granulated by twin-screw and single-screw extrusion. The particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen, a homogenizing silo, etc.; Silane adsorption process: when the particles are cooled to no more than 50° C., the prepared particles are added to a high-speed mixer, and the remaining 1 wt % of SEBS powder is added at the same time, and then the silane dissolved with an initiator is added while stirring. After the silane is added, it is stirred for 1 minute and then vacuum-packaged to obtain a silane masterbatch.

[0062] Test standards for the test samples obtained in Examples 1-3 and the test samples obtained in the comparative example:

[0063] The hardness test is carried out in accordance with the provisions of standard GB / T 2411, and the sample thickness is about 6.0 mm.

[0064] The tensile strength and elongation at break tests were carried out in accordance with the provisions of standard GB / T 1040.3, with a sample thickness of approximately 1.0 mm and a test speed of 250 mm / min.

[0065] The thermal elongation performance was tested in accordance with the provisions of standard GB / T 5470, with a test temperature of approximately 200°C, a test time of 15 min, a test load of 0.2 MPa, and a sample thickness of approximately 1.0 mm.

[0066] The volume resistivity is carried out in accordance with the provisions of standard GB / T 31838.2, and the sample thickness is about 1.0 mm. Table 1 Performance of Examples and Comparative Examples Note 1: The above properties are the test results after cross-linking at 80℃ for 4 hours. Note 2: Calculation basis of unit energy consumption of silane adsorption: The power of the high mixer used for silane adsorption in the embodiment and comparative example 1 is 50kW, the stirring time of each unit is 1 minute, the processing capacity is 100kg, the time required to produce 1 ton of product is 10 minutes, and the energy consumption is 50×10÷60≈8.3kW. In comparative example 2, silane adsorption is based on the process of one-step silane cross-linked polyethylene, the equipment heating power is 48kW, the motor and inverter power are both 7.5kW, and the heating time required to produce one unit (one unit with a production of about 1 ton) is about 120 minutes (rotation stirring time is about 70 minutes, vacuuming time is about 10 minutes, and raw material drying is about 40 minutes), and the unit energy consumption is 48×2+70×(7.5+7.5)÷60=113.5kW (vacuuming energy consumption is not calculated). Note 3: Silane adsorption production efficiency, the stirring time of each unit of the high mixer for silane adsorption in the embodiment and comparative example 1 is 1 minute, and the processing capacity of each unit is 100kg. As long as the front-end production can keep up or several production lines share one high mixer, 60 units, i.e. 6 tons, can be produced per hour. In comparative example 2, the process for silane adsorption of silane cross-linked polyethylene in one step is used, and the output per unit is about 1 ton, and the time per unit is about 70 minutes (only the rotation stirring time is calculated), so the production capacity per unit time is about 1×60÷70=0.857 tons. If the whole process time is 120 minutes, the production capacity is only 0.5 tons.

[0067] As can be seen from Table 1, the sample prepared according to the formula and process of the present invention can be cross-linked stably and quickly, and the tensile strength, elongation, electrical properties, etc. after cross-linking are good, and it has low hardness and good flexibility. By using the process of the present invention, the energy consumption of the silane adsorption process is greatly reduced, the reduction is more than 90%, the production efficiency is increased by about 6 times, and the effect of reducing consumption and increasing efficiency is very significant.

[0068] The above embodiments do not limit the present invention in any way, and any technical solutions obtained by equivalent replacement or equivalent transformation fall within the protection scope of the present invention.

Claims

1. One-step silane cross-linked SEBS-based elastomer, characterized by: It consists of two parts: a silane masterbatch and a catalyst masterbatch, wherein the mass ratio of the silane masterbatch to the catalyst masterbatch is 19:1; The silane masterbatch comprises the following components by weight: 40-60 parts of SEBS, 40-60 parts of linear low-density polyethylene, 1.5-5.0 parts of vinyl silane, 0.03-0.25 parts of initiator, 0.5-1.0 parts of lubricant, 20-30 parts of processing base oil, and 1.0-5.0 parts of antioxidant; The catalytic masterbatch comprises the following components in parts by weight: 99 parts of linear low-density polyethylene, 1 part of SEBS, 1.5-2.5 parts of catalyst, and 2.0 parts of antioxidant.

2. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The SEBS is a medium-low molecular weight product, wherein the styrene content is 18 wt %.

3. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: Under the conditions of a temperature of 190° C. and a load of 2.16 kg, the mass flow rate of the linear low-density polyethylene melt is 1 to 3 g / 10 min.

4. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The processing base oil has a flash point above 260°C.

5. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The initiator is dicumyl peroxide.

6. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The antioxidants in the silane masterbatch and the catalyst masterbatch are antioxidants 1010, 168 and 1024 compounded in a ratio of 1:1:

1.

7. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The vinyl silane is vinyl trimethoxy silane.

8. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The lubricant is PE-based silicone masterbatch, and the silicone content is 50wt%.

9. The one-step silane cross-linked SEBS-based elastomer according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

10. The method for preparing a one-step silane cross-linked SEBS-based elastomer according to any one of claims 1 to 10, characterized in that: The following steps are involved: (1) Preparation of silane masterbatch Add linear low-density polyethylene, lubricant, antioxidant, 99wt% SEBS powder and processing base oil to a high-speed mixer and stir evenly to make SEBS fully absorb the processing base oil, then add the materials to an internal mixer, internally mix to 140-160°C to fully plasticize the materials, then pour the material mass into a conical feeder, granulate through twin-screw and single-screw extrusion, cool and homogenize the particles through a pipeline, a cyclone separator, a vibrating screen and a homogenizing silo, add the particles to a high-speed mixer when the particles are cooled to no more than 50°C, add the remaining 1wt% SEBS powder at the same time, then add vinyl silane dissolved with an initiator, stir for 1 minute after the silane is added, and then vacuum pack to obtain a silane masterbatch; (2) Preparation of catalytic masterbatch The linear low-density polyethylene, SEBS powder, catalyst and antioxidant are mixed evenly in a high-speed mixer and then put into an internal mixer for internal mixing at 140-160°C to fully plasticize the materials. The material mass is then poured into a conical feeder for granulation through twin-screw and single-screw extrusion. The particles are cooled and homogenized through a pipeline, a cyclone separator, a vibrating screen and a homogenizing silo to obtain a catalytic masterbatch. (3) Packing the silane masterbatch and the catalyst masterbatch separately according to the ratio to obtain the finished product.